Gençlik ve spor genel müdürlüğü merkez ve taşra teşkilatının finansal kaynaklar açısından değerlendirilmesi - Bayansalduz, Mehmet (My University, 2002)
Bu çalışma ile Gençlik ve Spor Genel Müdürlüğü (GSGM) merkez ve taşra teşkilatı finansal kaynakları bakımından araştırılarak değerlendirilmeye çalışılmıştır. Bu amaçla, GSGM merkez ve taşra teşkilatı resmi dokümanları, TBMM bütçe görüşme tutanakları ve Türk spor yönetiminin tarihi süreç içinde gelişimine ilişkin kaynaklara yönelik olarak tarama yöntemi uygulanmıştır. Buna göre, kuruluşundan günümüze kadar GSGM'nin geçirdiği yapısal değişiklikler, merkez ve taşra teşkilatı örgütlenmesi, yönetim yapısı ve anlayışı, finansal kaynakları ve bu kaynakların kullanımı araştırılarak öncelikle mevcut durum tespit edilmeye çalışılmıştır. Ayrıca, GSGM merkez ve taşra teşkilatı yönetici ve personelinin yönetim uygulamaları ve finansal kaynak arttırıcı tedbirlere ilişkin görüş ve önerileri anket uygulaması ile alınmaya çalışılmıştır. Nitekim bu çalışma ile elde edilen bilgilere göre, devlet bütçesinden katma bütçeli olan GSGM'ye aktarılan kaynakların yeterli olmadığı, devletin kaynak oluşturacak yasal düzenleme ve kararları almadığı, mevcut merkeziyetçi yönetim yapısı ile GSGM kaynaklarının verimli olarak kullanılmadığı, taşra teşkilatının ise özel bütçeli olmasına rağmen bütçesinin ¾'ünden fazlasını GSGM'den alınan yardımların oluşturduğu, giderlerinin 9/ 10 kadarının cari harcamalar olduğu ve yatırım harcamalarının genel giderler toplamı içerisinde 1/ 14 gibi oldukça düşük bir oranda gerçekleştiği tespit edilmiştir. Bu durumda devlet bütçesinden aktarılan kaynakların büyük bir kısmını taşra teşkilatına tahsis etmek zorunda kalan GSGM'nin makro planlama ve hedefleri gerçekleştiremediği gibi, sportif faaliyet ve hizmetlerin verilmesinde de verimli ve etkili olamadığı anlaşılmıştır. Buna göre, Türkiye'de sporun geliştirilerek yaygınlaştırılabilmesi için bir çok kriterin göz önüne alındığı, ulusal düzeyde maddi kaynakların harekete geçirilerek tüm kesimlerin katılımının sağlandığı yeni spor politikaları oluşturulmalıdır. Zira bu görev salt ilgili bakanlık ve ona bağlı GSGM'nin göstereceği performansa bağlı olmamalıdır. Bunun için diğer bakanlıklar ve kamu kuruluşları, üniversiteler, özel sektör kuruluşları ve gönüllü kuruluşlarla işbirliği sağlanmalı, sporda ileri ülkelerde olduğu gibi spor saha ve tesislerinin yapım, bakım, onarım ve işletilmesinde mahalli idarelere yetki ve sorumluluk verilmelidir. Sonuç olarak, toplumsal gereksinimleri karşılayabilmek için gençlik ve spor yönetiminde insan merkezli, demokratik, katılımcı, dinamik, etkinliği ve verimliliği gözeten, özerk, yönetim ve hizmette kaliteyi temel alan bir spor yönetim modeli için köklü yapısal değişiklik ve yeniden yapılanma zorunludur. 2.

EVALUATION OF CENTRAL AND LOCAL ORGANIZATIONS OF THE GENERAL DIRECTORATE FOR YOUTH AND SPORT ON THEIR FINANCIAL SOURCES This study aims at the evaluation of central and local organizations of The Turkish Republic Prime Minister General Directorate for Youth and Sport through resarches on their financial sources. For this purpose a survey method was applied directed to offical documents on the central and local organizations of The General Directorate for Youth and Sport, the minutes of Turkish Parliament and the sources on the development of the management of Turkish sports through its historical process. According to this, it was our first objective to determine the present situation through the researches on organizational changes The General Directorate for Youth and Sport has undergone since its establishment, the organization of central and local organization, the construction and the mentality of the organization, its financal resources and the use of these resources. In addition to this, we have tried to obtain the opinions suggestions of the administrational implementations and financial source increasing precautions of the management and staff of The General Directorate for Youth and Sport central and local organizations. According to information obtained by these studies it was detected that the financial resources transferred from the state budget to The General Directorate for Youth and Sport, which has a supplementary budget, are inadequate, that the state doesn't take the measures which will provide resources, that The General Directorate for Youth and Sport resources aren't used efficiently due to the present central management, that, in spite of having a private budget, more three fourths of local organizations budget is provided by the financial aid from The General Directorate for Youth and Sport, that nine tenths of its expenditures are current expenditures and that investment expenditures are realized as low as one fourteenths within the sum of general expenditures. In this case it is understood that The General Directorate for Youth and Sport, which is forced to allot a great part of the sources transferred from state budget to local organizationis, is neither able to realize macro planning objectives nor efficient and competent in the provision of sports activites and services. According to this, in order to be able to develop and expand sports activities in Turkey, new sports policies must be formed allowing many criteria to be considered and the participation of all social groups by benefiting from all financial sources at national level. This duty must not only be dependent on the performance by the related ministry and The General Directorate for Youth and Sport. Inorder to achive this, cooperation among other ministeries and public institutions, universities, private sector organizations and volunteer institutions must be ensured and local authorities must be given authority and responsibility in the construction, maintenance, repair and management of sport fields and complexes as in the developed countries. Consequently, in order to be able to satisfy social needs, radical structural change and reconstructionalization are essential to achive a sports management model under the management of The General Directorate for Youth and Sport, which is human centered, democratic, participative, dynamic, autonomous, which observes efficiency and competency and which takes quality as the basis both in the management and service.
Keywords: Beden Eğitimi Ve Spor; Genç insanlar; Sosyal guruplar; Spor-yönetim-Türkiye; Toplum bilimleri; Yaş gurupları